2022
DOI: 10.1371/journal.pone.0261000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soluble guanylate cyclase stimulator on renal function in ZSF-1 model of diabetic nephropathy

Abstract: Background Diabetic nephropathy is associated with endothelial dysfunction and oxidative stress, in which the nitric oxide-soluble guanylate cyclase-cyclic guanosine monophosphate (NO-sGC-cGMP) signaling pathway is impaired. We hypothesize that sGC stimulator Compound 1 can enhance NO signaling, reduce proteinuria in a diabetic nephropathy preclinical model with diminished NO bioavailability and increased oxidized sGC. Therefore, we evaluated the effect of sGC stimulator Compound 1 on the renal effect in obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
1
3
0
2
Order By: Relevance
“…The praliciguat sGC stimulator led to a reduction in proteinuria that was more pronounced at the higher dose, although all praliciguat doses used were below the threshold for a significant reduction in blood pressure. These data are in line of a treatment study with an undisclosed sGC stimulator (Compound 1) in ZSF1 rats which also showed a reduction in proteinuria in a chronic treatment study [23]. These are very interesting findings, as sGC stimulators target the native wild-type form of sGC, and their efficacy is limited under oxidative stress.…”
Section: Discussionsupporting
confidence: 79%
“…The praliciguat sGC stimulator led to a reduction in proteinuria that was more pronounced at the higher dose, although all praliciguat doses used were below the threshold for a significant reduction in blood pressure. These data are in line of a treatment study with an undisclosed sGC stimulator (Compound 1) in ZSF1 rats which also showed a reduction in proteinuria in a chronic treatment study [23]. These are very interesting findings, as sGC stimulators target the native wild-type form of sGC, and their efficacy is limited under oxidative stress.…”
Section: Discussionsupporting
confidence: 79%
“…С учетом предварительных данных о возможных благоприятных нефротропных эффектах [85,86] и хорошей клинической переносимости верицигуата допускалось включение в исследование VICTORIA пациентов со сниженной скоростью клубочковой фильтрацией (до 15 мл/мин/1,73 м 2 ), а гиперкалиемия не была критерием исключения [75]. Полученная благодаря этому информация представляет ценность для клинической практики, так как подобные нарушения часто встречаются у пациентов с СН и негативно влияют на прогноз, а возможности лечения при этом очень ограничены как изза побочных эффектов, так и малой изученности лекарственных средств в таких ситуациях.…”
Section: Socrates-preserved (Ii фаза снсфв) [3]unclassified
“…С учетом предварительных данных о возможных благоприятных нефротропных эффектах [85,86] и хорошей клинической переносимости верицигуата допускалось включение в исследование VICTORIA пациентов со сниженной скоростью клубочковой фильтрацией (до 15 мл/мин/1,73 м 2 ), а гиперкалиемия не была критерием исключения [75]. Полученная благодаря этому информация представляет ценность для клинической практики, так как подобные нарушения часто встречаются у пациентов с СН и негативно влияют на прогноз, а возможности лечения при этом очень ограничены как изза побочных эффектов, так и малой изученности лекарственных средств в таких ситуациях.…”
Section: Socrates-preserved (Ii фаза снсфв) [3]unclassified